Building the Entrepreneurial Spirit of Santri through Entrepreneurship Classes at Hidayatul Mubtadiien Islamic Boarding School Santri, Riau Province - Zaitun Zaitun; Kholid Junaidi; Annisa Fazila Sabrina Damanik (Program Pascasarjana Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study focuses on cultivating the entrepreneurial spirit among santri (students) through dedicated entrepreneurship classes at Hidayatul Mubtadiien Islamic Boarding School in Riau Province. The research aims to assess the effectiveness of integrating entrepreneurship education into the curriculum to empower santri with essential entrepreneurial skills. The methodology involves a comprehensive analysis of the entrepreneurship classes' impact on the mindset, knowledge, and practical abilities of the santri. Through surveys, interviews, and performance evaluations, the study aims to provide insights into the effectiveness of the entrepreneurship program in fostering an entrepreneurial mindset and preparing santri for real-world business challenges.